2015
DOI: 10.17554/j.issn.2409-5680.2015.01.23
|View full text |Cite
|
Sign up to set email alerts
|

Initial Late Probing for Congenital Nasolacrimal Duct Obstruction, Rate of Success and Factors Associated with Failure

Abstract: AIM: Evaluation of the efficacy of initial late probing for congenital nasolacrimal duct obstruction and identifying the risk factors associated with failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…The overall cure rate of probing for different studies varies from 84% to 92%. 14,[20][21][22] In this study, an overall success rate of 88% was found, which is consistent with the results of these researchers. This high efficiency gives a good prognosis of surgical treatment of nasolacrimal duct probing at all.…”
Section: Discussionsupporting
confidence: 90%
“…The overall cure rate of probing for different studies varies from 84% to 92%. 14,[20][21][22] In this study, an overall success rate of 88% was found, which is consistent with the results of these researchers. This high efficiency gives a good prognosis of surgical treatment of nasolacrimal duct probing at all.…”
Section: Discussionsupporting
confidence: 90%